MENGEMBANGKAN KEMAMPUAN SCRUM MASTER DALAM BIDANG PEMASARAN - Sofyan Mufti Prasetiyo; Khafid Nur Ilyas; Muhammad Helmi; Wahyu Aji Firmansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Scrum Masters are experts who understand Scrum's methods and functions in project management. A person in this role has full responsibility for communicating information to anyone using this methodology so that they fully understand Scrum. The Scrum Master must also always understand the Scrum values of Commitment, Courage, Focus, Openness, and Respect. Judging from its value and nature, it can be said that the Scrum Master is the leader of project development. However, a Scrum Master differs from a project project in that it focuses on how the project progresses on time and on budget. By doing this, the Scrum Master focuses more on how the team can complete the development of the project according to the everyday Scrum paradigm method.